Seguimiento de pacientes con catéter venoso periférico asociado a tiempos de permanencia y complicaciones. Hospital Sagrado Corazón de Jesús Quevedo. Periodo. mayo-agosto 2023 - Avilés Llumiguano, Ana Isabel (2023)
The objective of this research work is to determine the follow-up of patients with peripheral venous catheter associated with length of stay and complications. It is a descriptive-quantitative, bibliographic, bibliographic, descriptive-quantitative, bibliographic study, with the results obtained from the research, to be carried out at the Hospital Sagrado Corazón de Jesús Quevedo, period May-August 2023, ending with the training of the nursing staff of the internal medicine area. It is a descriptive-quantitative, bibliographic study, with a cross-sectional and field design with a non-experimental approach, which included the participation of 34 patients who have undergone peripheral venous catheter placement during the period July 2023 in the area of Internal Medicine of the Sacred Heart of Jesus Hospital; to obtain the information, an observation guide was applied with sections on sociodemographic data, complications and peripheral venous catheter permanence times. The results obtained in this research show that the most prevalent complication in patients with peripheral venous catheter is phlebitis and it is more frequent in the adult population with an age range between 40 and 61 years, the catheter caliber most used by the professional is 20G and 22G in this hospitalization service due to the age of the patients treated, the appearance occurs in most cases when administering medication. However, phlebitis emerges as a concern. Key words: follow-up, peripheral venous catheter, dwell time, complications.